THE EFFECTIVENESS OF MASSAGE THERAPY IN REDUCING PAIN IN POSTPARTUM MOTHERS: A LITERATURE REVIEW - Sukmawati, Sukmawati; Kosim, Kosim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2026)
Pain can be experienced by mothers during labor or after labor (postpartum), which can disrupt the mother's comfort and activities. This must be handled quickly and appropriately to prevent more serious complications, one of which is related to massage therapy. The purpose of this study was to determine the effectiveness of massage therapy in reducing pain in postpartum mothers. The research method used was a literature review, with articles searched through Scopus, PubMed, and Medline databases. The inclusion criteria were randomized controlled trials (RCTs), quasi-experimental studies (QE), experimental studies, and comparative studies, all of which used primary data, articles published between 2019 and 2024, study population of postpartum mothers, independent variable of massage therapy and dependent variables of pain in postpartum mothers, articles in Indonesian and English, accessible, and available in full text. The keywords used were